A child feeding index is superior to WHO IYCF indicators in explaining length-for-age Z-scores of young children in rural Cambodia. (13th May 2015) - Reinbott, Anika; Kuchenbecker, Judith; Herrmann, Johannes; Jordan, Irmgard; Muehlhoff, Ellen; Kevanna, Ou; Krawinkel, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Adequate young child feeding practices are influenced by a multitude of factors which affect growth and development. A combination of indicators is needed to explain the role of complementary feeding practices in growth retardation. Methods: A cross-sectional nutrition baseline survey was conducted in rural Cambodia in September 2012. Villages in pre-selected communes were randomly selected using stunting as a primary indicator. Data were collected from 803 randomly selected households with children aged 6–23 months, based on a standardised questionnaire and on length/height and weight measurements of mother and child. WHO Infant and Young Child Feeding (IYCF) indicators [minimum dietary diversity (MDD), minimum meal frequency (MMF), minimum acceptable diet (MAD)] and a child feeding index (CFI) were created. The latter consisted of five components: breastfeeding, use of bottle, dietary diversity, food frequency and meal frequency which were adjusted for three age groups: 6–8, 9–11 and 12–23 months. The highest possible score was 10. Associations between length-for-age Z-scores (LAZ) and WHO indicators or CFI were explored. Results: Mean (SD) LAZ was −1·25 (1·14) (n = 801). Mean (range) CFI was 6·7 (1–10) (n = 797). Mean CFI was highest in the 9–11-months age group (7·93) and lowest for those aged 12–23 months (5·96). None of the WHO IYCF indicators was associated with LAZ, whereas CFI showed significant association with LAZ (P < 0·01). The association between higher CFI scores and LAZ became weaker as age increased. Conclusion: The results highlight the need to include a wide range of information in the analysis in order to understand the association between appropriate infant feeding practices and child growth.